Evaluation of policies on community participation in the planning, implementation, and monitoring of health programs at the local level: A literature review - Sudarningayuti Lintang Wahyu Azahra; Nadia Hafrisa; Della Dwi Ayu; Riswandy Wasir (Indonesian Journal of Health Science, 2026)
Community participation is a crucial element in health development efforts because the success of health programs depends heavily on the active involvement of the community, whether in the form of labor, ideas, or other forms of support. Community participation is necessary to assist the government in achieving its goals of improving health outcomes. Such participation is not merely defined by physical presence but also encompasses the community’s mental and emotional engagement in supporting development activities. Therefore, community involvement needs to be enhanced at various stages of activities, including in the implementation and monitoring of health programs at the local level. A literature review method was employed by searching for scientific articles through the Google Scholar, Garuda, and PubMed databases. Inclusion criteria focused on qualitative and quantitative studies regarding the evaluation of community participation published within the last five years. The selected articles were those relevant to the topic and aligned with the research objectives. An evaluation of community participation policies in the planning, implementation, and monitoring of health programs at the local level indicates that community involvement remains suboptimal. This is due to a lack of knowledge and awareness among the public, limited communication, and a lack of community involvement in health decision-making. During the implementation phase, a participatory approach through health education, outreach, community-based communication, and the empowerment of health volunteers can increase community involvement in health programs. However, during the monitoring phase, the community still does not play a significant role in evaluating health policies.